Optimal Wastewater Treatment Design by Using Genetic Algorithm (University of Thi-Qar Journal for Engineering Sciences, 2015)
Integrated advanced wastewater treatment provides important fundamental solutions to problems associated with water scarcity prevailing in arid and semi-arid climatic regions.This was accomplished through treated water with specific specification and characteristics suitable to be used for agricultural, domestic, and industrial purposes. This study is concerned with the use of genetic algorithm procedure for the optimum design of integrated advance wastewater treatment units, with their various types and characteristics. The aim of optimum wastewater treatment units design is to attain optimum values of certain pre-defined objective function. The objective function is to satisfy certain constraints and achieve minimum capital, maintenance, and operation costs.Chemical clarification treatment unit was used in this study.This study includes development of computer program for advances wastewater treatment plants design adopting genetic algorithm. The program was developed using Matlab software. The results obtained from this study include the finding of optimum design criteria for advanced wastewater treatment plants. The obtained design criteria are satisfying the required water quality with minimum treatment cost.